2018
DOI: 10.3892/ijo.2018.4551
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 on circulating epithelial tumor cells correlates with the proliferation marker, Ki-67, and may be associated with the aggressiveness of tumors in breast cancer patients

Abstract: Circulating epithelial tumor cells (CETCs) in peripheral blood are a prerequisite for the development of metastases. B7-H3 is an important immune checkpoint member of the B7 family and inhibits T-cell mediated antitumor immunity. Its expression is associated with a negative prognosis and a poor clinical outcome. Based on the clinical success of inhibitory immune checkpoint blockade, monoclonal antibodies (mAbs) against B7-H3 appear to be a promising therapeutic strategy. The proliferation biomarker, Ki-67, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…However, radioresistance, resulting in tumor recurrence and a poor prognosis, is still a major reason for treatment failure 2 . Previous studies have indicated that B7-H3 regulates various tumor biological processes, including radioresistance 14,25 . Consistent with these findings, we found that the B7-H3 mRNA and protein expression levels were significantly increased in CRC cells after X-ray irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, radioresistance, resulting in tumor recurrence and a poor prognosis, is still a major reason for treatment failure 2 . Previous studies have indicated that B7-H3 regulates various tumor biological processes, including radioresistance 14,25 . Consistent with these findings, we found that the B7-H3 mRNA and protein expression levels were significantly increased in CRC cells after X-ray irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…immunologic and nonimmunologic functions of B7-H3 in tumors 7,10,14,25 , it will be valuable to develop blocking antibodies against B7-H3 for tumor therapy. 8H9, which targets B7-H3, combined with craniospinal irradiation has been determined to prolong the survival of patients with metastatic central nervous system neuroblastoma 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Recent studies have demonstrated that Ki-67 is closely associated with cell proliferation (20,21). Investigating the levels of Ki-67 showed that miR-520a-3p mimics significantly decreased Ki-67 expression in GC cells (P<0.01; Fig.…”
Section: Mir-520a-3p Suppresses the Proliferation Of Gc Cellsmentioning
confidence: 99%
“…The expression of another important immune checkpoint member, B7-H3, on CTCs of breast cancer patients has been also reported. The B7-H3 positive CTCs showed pronounced correlation with Ki-67 expression, a tumor proliferation marker, and were proposed to be a potential biomarker or target for immune checkpoint blockade therapies in breast cancer (Pizon et al, 2018). CTCs are valuable source of tumor information to develop new biomarkers, however, there are some challenges on the reproducibility of the results which are linked to the applying various techniques for isolation and enriching of these cells.…”
Section: Liquid Biopsies Biomarkersmentioning
confidence: 99%